Konsep Pendidikan Multikultural dalam Pandangan Banks - Mo’tasim, Mo’tasim; Mollah, Moh. Kalam; Nurhayati, Ifa (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2022)
This article aims to discuss multicultural education in James Bank's view. This study uses a qualitative research approach with library research using Banks' views as the main reference and several other scientific journal documents as comparison data for the analysis of Banks' views. The research found that James A. Banks, the first black professor to be employed by the College of Education, will retire in January after teaching at UW for half a century. Known worldwide for his pioneering scholarship in the field of multicultural education, According to Banks the dimension of multicultural education. there are 5 dimensions of multicultural education that must exist in multicultural education. The first is the integration of multicultural education in the curriculum, the second is the construction of science. Third, the reduction of prejudice, fourth. An equity pedagogy, the fifth is the empowerment of school culture and social structure. The bank with five dimensions opens a bright way in answering the western debate about disparity and grouping an ethnicity and culture. Bank-style multicultural education is very suitable to be applied to the spirit of national education